Procuring Survival - Matilde Cappelletti; Leonardo M. Giuffrida; Gabriele Rovigatti (The Journal of Industrial Economics, 2024)
We investigate the impact of public procurement on business survival. Using Italy as a laboratory, we construct a large-scale dataset of firms—covering balance-sheet, income-statement, and administrative records—and match it with public contract data. Employing a regression discontinuity design for close-call auctions, we find that winners are more likely to stay in the market than marginal losers after the award and that the boost in survival chances lasts longer than the contract duration. We document that this effect is associated with earnings substitution rather than increased business scale and that survivors experience no productivity premium. Securing contracts relaxes credit constraints and acts as a mechanism for survival.
Keywords: 330